Parental Identity, Governmentality and Retroactive Empowerment: Towards a Democratic School Space - Mendel, Maria (International Journal about Parents in Education, 2023)
In the paper I present a way of theorizing parent identity work using the analytic lens of governmentality. Among the revisited biographical narratives of the parents, many contain unifications directly pertaining to the governmental character of their learning experiences. Based on the contents of these texts, one could say that governmental learning leads the subject to the internalization of externally executed formative practices. In other words, the conduct of conduct (one of the dimensions of Foucauldian governmentality) appears to be the condition of the internalization of the external, and, thus, of personal identity. In light of this study, on the one hand, parental identity can be perceived as a product of permanent governing by various pacts/partnerships in the “pedagogised society” but, on the other, the governmental character of educational experiences empower parents. I argue that parents need empowerment and to know themselves as parents. Thus, they can become active partners in the democratically governed space of the school. The study discovers the significance of retroactivity in the construction of parental identity and shows the ways through which schools and teachers can use it in their democratic co-operation with parents.